Reciprocal interactions between tumor and endothelial cells: Effects of selective vasopressin V2 receptor peptide agonists - Garona, Juan (2014)
Recent experimental evidence suggested that the synthetic peptide desmopressin (DDAVP) interferes tumor angiogenesis by inducing the formation of angiostatin. It is also known that DDAVP stimulates the endothelial release of von Willebrand factor, a key element in resistance to metastasis. Vasopressin V2 receptor agonists such as DDAVP seem to evoke dual angiostatic and antimetastatic effects, breaking cooperative interactions of tumor and endothelial cells during tumor progression.